A multi-objective and integrated model for supply chain scheduling optimization in a multi-site manufacturing system. Issue 9 (2nd September 2018) - Beheshtinia, Mohammad Ali; Ghasemi, Amir
ABSTRACT: In a supply chain, scheduling plays a significant role in coordinating and cooperation. This article considers an integration of supplier and vehicle scheduling problems in terms of vehicle routing determination for transporting raw materials from the suppliers to some manufacturing centres. The aim is to minimize the total tardiness of all assigned orders to the suppliers and simultaneously minimize the total travelled distance of the vehicles. Most manufacturing companies, which have to manage their suppliers as an industrial unit, experience this problem. A new metaheuristic algorithm called the multiple league championship algorithm (MLCA), inspired by championship matches, is proposed to solve this problem. To show the efficiency of MLCA, it is compared with two different algorithms used for the problems in the literature that are closest to this problem and a soccer-based algorithm called golden ball. The experimental results prove that the proposed algorithm has better performance than these algorithms.